Behavioral activation group therapy for reducing depressive symptoms and improving quality of life: a feasibility study. Issue 1 (December 2016) - Samaan, Zainab; Dennis, Brittany; Kalbfleisch, Lindsay; Bami, Herman; Zielinski, Laura; Bawor, Monica; Litke, Kathryn; McCabe, Kathleen; Whattam, Jeff; Garrick, Laura; O'Neill, Laura; Tabak, Terri; et al.
Abstract Background Depression is associated with a loss of productivity and noticeable personal, social, and economic decline; it affects more than 350 million people worldwide. Behavioral activation (BA), derived from cognitive behavioral therapy, has drawn increasingly more interest as a means of treatment for major depressive disorder due to its relative cost-effectiveness and efficacy. In this study, we disseminate findings from a feasibility study evaluating barriers to implementing a group BA program for major depressive disorder. The purpose of this feasibility study is to assess both patient and clinician perceptions on components of a group-based behavioral activation (BA) program. In particular, this feasibility study provides in-depth evaluation of the acceptability of BA prior to the design and implementation of a randomized trial to investigate BA effectiveness. Findings from this study directly informed decisions regarding the design and implementation of BA during the pilot trial. Specific components of BA were assessed and modified based on the results of this study. Methods This qualitative study was completed through the Mood Disorders Program at St. Joseph's Healthcare Hamilton. The authors of this study used data from two focus group sessions, one consisting of an interdisciplinary group of clinicians working in the Mood Disorders Program, and the other of registered outpatients of the Mood Disorders Program with a confirmed clinical diagnosis of depression. The benefits of offering this program in a group format, mainly social skill development opportunities and the use of technology such as activity tracking device, smart phones, and tablets during the therapy sessions, are a major focus of both the clinician and patient groups. Both groups emphasized the importance of offering sustainable activation. Results Differences in opinions existed between staff and patient groups regarding the use of technology in the program, though ultimately it was agreed upon that technology could be useful as a therapeutic aid. All participants agreed that behavioral activation was essential to the development of positive habits and routines necessary for recovery from depression. Patients agreed the program looked sustainable and stressed the potential benefit for improving depressive symptoms. Conclusions Discussions from clinician and patient-centered focus groups directly informed decisions regarding the design and implementation of BA during the pilot trial. Specific components of BA were assessed and modified based on the results of this study. These findings provide insight for clinicians providing behavioral activation programming, and will serve as a framework for the development of the Out of the Blues program, a group-based BA program to be piloted in the Mood Disorders Program at St. Joseph's Healthcare Hamilton. Trial registration Clinical Trials registration numberNCT02045771